Vocabulary Mastery Through the Application of Visual Auditory Kinesthetic (VAK) - Udju, Jemmy Patrisius Oes (BAHTRA: Pendidikan Bahasa dan Sastra, 2022)
Vocabulary mastery is essential to support the four language skills and determine a student's communication success after grammatical competence. Lexical competence is assumed to be second only to grammar. One alternative in vocabulary teaching is Visual Auditory Kinesthetic (VAK). This classroom action research (CAR) aims to apply VAK because of students' difficulties in memorizing new vocabulary, especially abstract nouns. The CAR procedure consists of planning, action, observation, and reflection. Each stage has activities to achieve research objectives. The subject of this study was an Seventh Grade student of SMPN Haliulun. There are vocabulary tests, questionnaires, and observation sheets as research instruments. Then, the data is analyzed using both quantitatively and qualitatively. Findings from the vocabulary test showed that 20 out of 24 students passed the minimum sedentary criteria or the average score fell on 77. It turns out that students participate actively, pay good attention to the material and show enthusiasm in English classes. It can be concluded that the application of VAK can not only improve students' vocabulary mastery but also class participation. In addition, the results of current research prove that the application of VAK as an alternative to teaching can lead students in memorizing abstract vocabulary.